Theory of mind and facial emotion recognition in adults with temporal lobe epilepsy: A meta-analysis - Qi, Liang; Zhao, Jing; Zhao, PanWen; Zhang, Hui; Zhong, JianGuo; Pan, PingLei; Wang, GenDi; Yi, ZhongQuan; Xie, LiLi (Frontiers in Psychiatry, 2022)
Background: Mounting studies have investigated impairments in social cognitive domains (including theory of mind [ToM] and facial emotion recognition [FER]) in adult patients with temporal lobe epilepsy (TLE). However, to date, inconsistent findings remain. Methods: A search of PubMed, Web of Science, and Embase databases was conducted until December 2021. Hedges g effect sizes were computed with a random-effects model. Meta-regressions were used to assess the potential confounding factors of between-study variability in effect sizes. Results: The meta-analysis included 41 studies, with a combined sample of 1749 adult patients with TLE and 1324 healthy controls (HCs). Relative to HCs, adult patients with TLE showed large impairments in ToM (g = −0.92) and cognitive ToM (g = −0.92), followed by medium impairments in affective ToM (g = −0.79) and FER (g = −0.77). Besides, no (statistically) significant differences were observed between the magnitude of social cognition impairment in adult with TLE who underwent and those who did not undergo epilepsy surgery. Meta-regressions exhibited that greater severity of executive functioning was associated with more severe ToM defects, and older age was associated with more severe FER defects. Conclusions: Results of this meta-analysis suggest that adult patients with TLE show differential impairments in the core aspects of social cognitive domains (including ToM and FER), which may help in planning individualized treatment with appropriate cognitive and behavioral interventions.